Diagnostic Accuracy of Magnetic Resonance Spectroscopy in Differentiating Malignant and Benign Brain Lesions - Khalid javed, Hira Ashfaq Butt, Hafiz M. Amir Jamil, Asad Ullah Kamran, Beenish Nadeem, Fareeha Shahid, Islah Uddin, (Pakistan Journal of Medical & Health Sciences, 2023)
The aim of this study is to determine the diagnostic ability of magnetic resonance spectroscopy in separating malignant and benign cerebral masses, when histopathology taken as gold standard. The results of my study will not only resolve this controversy but also If MRS diagnostic accuracy will be found high in distinguishing ring enhancing lesions of brain, then this non-invasive modality can be applied routinely in our general practice for proper treatment selection the lesions in order to reduce the morbidity and mortality of these particular patients. Materials & Methods: We included around 141 cases presenting to us at the Radiology department of Sir Ganga Ram Hospital, Lahore, fulfilling the inclusion criteria was selected after we got approval for the study from IRB committee of university. Informed consent was taken from each patient. We performed magnetic resonance spectroscop in each case using 1.5 Tesla MR system having graded power of 33 mT/m and results of MRS were read and reported by one radiology consultant. Malignant or benign lesions were noted on MRS. After this, each patient was undergone biopsy in the concerned ward by the consultant neurosurgeon and tissue was sent to institutional pathology laboratory for histopathology. Histopathology results were interpreted by the consultant histopathologist (at least 3 years of post-fellowship experience) and benign or malignant lesion was noted Results: All the included cases underwent standard magnetic resonance spectroscopy (MRS) of brain. MRS strengthened the suspicion of malignant brain lesions in 94 (66.67%) cases. Histopathology findings confirmed malignant brain lesions in 90 (63.83%) cases. Conclusion: This study concluded that MRS is the non-obstrusive method of imaging with greater diagnostic accuracy in differentiating malignant and benign brain lesions, and that it has not only made drastically better our capability to identify malignant brain lesions preoperatively, and moreover assists neurosurgeons in taking much better decisions. As a result, we urge that MRS be performed habitually in all suspected instances of intracranial mass lesion for reliable pre-operative identification of malignant brain lesions and selection of appropriate surgical technique. Keywords: MRS. MRI. Brain lesions, brain tumor, CNS tumor, Magnetic resonance spectroscopy